Algorithm for analyzing the movement pattern of the temporomandibular joint musculararticular system based on multichannel electromyogram processing - I. V. Samuylov; М. V. Davydov; G. G. Sagaimaruf; I. N. Baradina; S. P. Rubnikovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
Musculoskeletal system disorders is one of the priority directions in dentistry. They can manifest as Kosten's syndrome, snapping jaw, painful dysfunction syndrome, increased tooth abrasion, splits, breaks, pain and spasms in muscles, etc. The study set the following objectives: to develop an algorithm for analyzing the movement pattern of the muscular-articular system by developing an algorithm for recording, analyzing, filtering and processing multichannel electromyograms of the maxillofacial muscles. Analysis of the proposed algorithm for processing multichannel electromyograms showed that 7.2 % of multichannel electromyograms could not be analyzed due to patients' violations of the movement algorithm; 8.7 % of electromyogram checkpoint values were corrected. The group without dysfunctions of the temporomandibular joint is characterized by the prevalence of the relaxation coefficient of the left temporal muscle over the coefficient of the right muscle. The dysfunctioned group has the opposite result. The value of the compression ratio of the temporal muscles exceeding 2.5 is typical for the group with dysfunctions of the temporomandibular joint. The studied groups differ as much as possible when analyzing the relaxation coefficients of the temporal muscles. When analyzing this coefficient, it was possible to truly determine the presence or absence of violations in 50 %, falsely – in 16 % of cases. The coefficient of relaxation of the masticatory muscles made it possible to obtain a true state of 24 %, a false one – in 8 %. We concluded that the compression ratio is less suitable for separating patients with and without dysfunction of the temporomandibular joint.